Freising and Worms in the early eleventh century: revisiting the relationship between the "Collectio duodecim partium" and Burchard's "Decretum" - Austin, Greta (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Kanonistische Abteilung, 2007)
Burchard von Worms, Liber decretorum (Decretum), Freising, Collectio duodecim partium.